The Labor Market Policy Reform Agenda in MENA - World Bank (World Bank, Washington, DC, 2012)
Despite positive economic growth in recent years, basic labor market outcomes in the Middle East and North Africa (MENA) remained stagnant and have only improved slightly in the past 10 years. A number of recent and ongoing analyses have stressed the pressing need for many economies in the region to identify new and sustainable sources of growth, create more and higher value-added employment, and absorb the fast growing number of university graduates into the labor market. Structural transformation towards higher productivity and the creation of qualified jobs requires far reaching reforms in multiple sectors, including innovation, science and technology; education quality; labor market flexibility and mobility; and entrepreneurial incentives allowing investors to innovate, invest, and create higher value added jobs. Within this broad context, this note focuses on labor market policies and the agenda for labor market reform in MENA.